2-Naphthylmethyl N-[1-(4-pyridyl)ethylidene hydrazinecarbodithioate - How, Fiona Ni Foong; Watkin, David J.; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim (International Union of Crystallography, 2007)
The molecules in the crystal structure of the title compound,C19H17N3S2, are linked by an intermolecular N—H N [2.839 (5) A ° ] hydrogen bond via the -N and the pyridyl N atoms. The thione S atom is in a trans position with respect to the methylpyridine fragment across the C—N bond but adopts a cis position with respect to the naphthalene ring across the C—S bond. There is a – stacking interaction between the naphthalene rings, with a centroid–centroid distance of 3.397 (2) A ° .